Gramene 2016: comparative plant genomics and pathway resources. Issue Volume 44:Issue D1(2016) (8th November 2015) - Tello-Ruiz, Marcela K.; Stein, Joshua; Wei, Sharon; Preece, Justin; Olson, Andrew; Naithani, Sushma; Amarasinghe, Vindhya; Dharmawardhana, Palitha; Jiao, Yinping; Mulvaney, Joseph; Kumari, Sunita; Chougule, Kapeel; et al.
Abstract: Gramene (http://www.gramene.org ) is an online resource for comparative functional genomics in crops and model plant species. Its two main frameworks are genomes (collaboration with Ensembl Plants) and pathways (The Plant Reactome and archival BioCyc databases). Since our last NAR update, the database website adopted a new Drupal management platform. The genomes section features 39 fully assembled reference genomes that are integrated using ontology-based annotation and comparative analyses, and accessed through both visual and programmatic interfaces. Additional community data, such as genetic variation, expression and methylation, are also mapped for a subset of genomes. The Plant Reactome pathway portal (http://plantreactome.gramene.org ) provides a reference resource for analyzing plant metabolic and regulatory pathways. In addition to ∼200 curated rice reference pathways, the portal hosts gene homology-based pathway projections for 33 plant species. Both the genome and pathway browsers interface with the EMBL-EBI's Expression Atlas to enable the projection of baseline and differential expression data from curated expression studies in plants. Gramene's archive website (http://archive.gramene.org ) continues to provide previously reported resources on comparative maps, markers and QTL. To further aid our users, we have also introduced a live monthly educational webinar series and a Gramene YouTube channel carrying video tutorials.